Word formation chains of denominal multistage derivatives with initial formant -iti in Slovenian - Kern Boris (Južnoslovenski Filolog)
The article presents and analyzes the suffix combinatorics exhibited by denominal multistage derivatives whose initial suffix is -iti. An examination of whether the semantic restriction of the corpus material (sensory perception) yields different word formation chains than the non-restricted one (material resulting from the KOBOS project, including BSSJ, SSKJ 2 and the Gigafida 2.0 corpus) revealed that the combinatorial picture is quite different. The KOBOS material shows that the combinatorics of the initial suffix -iti is among the most diversified, encompassing 36 different suffix chains. In the material derived from nouns denoting senses, the suffix -iti as a base formant appears in the following four word-formation chains: (1) -iti + -ati + -anje, (2) -iti + -ati + -alo + -ni, (3) -iti + -ati + -oč, (4) -iti + -ati + -n. The KOBOS material indicates that most sequences are bipartite: -iti + -ec, -iti + -ež, -iti + -ilec, -iti + -un, -iti + -ilka, -iti + -nica, -iti + -enje, -iti + -ø, -iti + -ka, -iti + -ina, -iti + -je, -iti + -išče, -iti + -eč. These are followed by tripartite chains: -iti + -itev + -en, -iti + -av + -elj, -iti + -el + -ost, -iti + -en + -ec, -iti + -en + -ik, -iti + -en + -ost, -iti + -ilen + -ik, -iti + -ljiv + -ost; and two quadripartite chains: -iti + -el + ina + -ica and -iti + -el + ina + -ast.